A method for strength calculation of a shaft of wells' sinker - Victor Lis; Yuriy Evgenievich Ponomarenko (Вестник СибАДИ, 2017)
The absence of a method for strength calculation of a shaft of wells’ sinker, considering its structural features, significantly complicates the constructor’s work in determining essential cross-sections of a shaft, providing its reliable, no-failure operation during the whole life cycle. The article provides the scheme of loading a rolling working element in a well, the scheme of a load transferring from rollers to the shaft’s core using off-center bushing. The authors of the article have also determined the influence of these bushings on load distribution along the core.